2018
DOI: 10.2147/cmar.s159441
|View full text |Cite
|
Sign up to set email alerts
|

Blockage of store-operated Ca<sup>2+</sup> entry antagonizes Epstein&ndash;Barr virus-promoted angiogenesis by inhibiting Ca<sup>2+</sup> signaling-regulated VEGF production in nasopharyngeal carcinoma

Abstract: BackgroundEpstein–Barr virus (EBV) actively contributes to the pathological process of nasopharyngeal carcinoma (NPC) by enabling NPC cells to acquire various capacities required for their malignant biological actions. Our earlier works demonstrated that EBV-encoded latent membrane protein 1 (LMP1) enhanced vascular endothelial growth factor (VEGF)-mediated angiogenesis by boosting store-operated Ca2+ entry (SOCE) upon extracellular epidermal growth factor (EGF) stimulation. However, the antagonistic effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 27 publications
3
23
0
Order By: Relevance
“…TRPC1 is a Ca2+-through pathway found in key metabolic organs and tissues, including hypothalamus, adipose tissue, and skeletal muscle. Deletion of TRPC1 may alter the regulation of cellular energy metabolism [36][37][38]. The TRPC1 promoter has 3 putative NF-κB binding sites.…”
Section: Discussionmentioning
confidence: 99%
“…TRPC1 is a Ca2+-through pathway found in key metabolic organs and tissues, including hypothalamus, adipose tissue, and skeletal muscle. Deletion of TRPC1 may alter the regulation of cellular energy metabolism [36][37][38]. The TRPC1 promoter has 3 putative NF-κB binding sites.…”
Section: Discussionmentioning
confidence: 99%
“…Further evidence has demonstrated that EBV-positive NPC cells are more tumorigenic and angiogenic in vivo than EBV-negative NPC cells (Ye et al, 2018). EBV is associated with high levels of VEGF and reduced survival of Hodgkin’s lymphoma patients (Koh et al, 2018).…”
Section: Epstein–barr Virusmentioning
confidence: 99%
“…In addition to NF-κB, STAT-3, and protein kinase C gamma (PKCγ) are essential for the LMP1-CTAR1-induced augmentation of EGFR activation (Kung and Raab-Traub, 2008). It is possible that through the activation of EGFR in NPC cells, EBV enhances calcium signaling that promotes VEGF expression (Ye et al, 2018). Together, these studies suggest that induction of both FGFR and EGFR contributes to LMP1-mediated angiogenesis.…”
Section: Epstein–barr Virusmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, researchers are not very knowledgeable about the complex pathogenesis of MDS. However, angiogenesis has been regarded as a vital pathophysiological process in solid tumors for tumor growth, proliferation, and metastasis . In addition, recent studies showed that angiogenesis and angiogenesis factors play a vital role in the onset and development of MDS and AML .…”
Section: Introductionmentioning
confidence: 99%